2012
DOI: 10.1590/s0102-09352012000400025
|View full text |Cite
|
Sign up to set email alerts
|

Farelo de manga na dieta de cordeiros em confinamento

Abstract:  RESUMOAvaliou-se o efeito da substituição do milho por farelo de manga em dietas para ovinos. As características avaliadas foram: consumo e digestibilidade aparente da matéria seca (MS), da proteína bruta (PB), da fibra em detergente neutro (FDN), da matéria orgânica (MO), do extrato etéreo (EE), da energia bruta (EB), da energia digestível (ED), dos carboidratos não fibrosos (CNF) e dos carboidratos totais (CT). Vinte e quatro cordeiros Santa Inês foram distribuídos em delineamento inteiramente ao acaso, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
2
3
0
Order By: Relevance
“…Some other studies utilizing the same roughage:concentrate ratio have found NDF digestibilities of 56.6 % in a diet with Tifton 85 hay (Costa et al 2012) and 78.7 % in a diet with fresh Elephant grass (Aragão et al 2012), which demonstrates compatibility of the values found in the present experiment with those found in the literature.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Some other studies utilizing the same roughage:concentrate ratio have found NDF digestibilities of 56.6 % in a diet with Tifton 85 hay (Costa et al 2012) and 78.7 % in a diet with fresh Elephant grass (Aragão et al 2012), which demonstrates compatibility of the values found in the present experiment with those found in the literature.…”
Section: Discussionsupporting
confidence: 88%
“…The diets with concentrate presented similar apparent DM digestibility to the values observed in diets with the same roughage:concentrate proportion using corn silage (Moreno et al 2010)-78.7 %; Elephant grass hay (Lima et al 2012)-80.1 %; and fresh Elephant grass (Aragão et al 2012), with 81.8 % of digestibility. Diet FU, which did not have concentrate feeds, showed an apparent DM digestibility close to the values observed by Bringel et al (2011) and Miotto et al (2012)-59.4 and 51.3 %, respectively-in diets with Elephant grass silage only.…”
Section: Discussionsupporting
confidence: 52%
“…Replacement of the corn grains (33%) by MSM was recommend by Silva et al (2016), because of the better fermentation of fiber carbohydrates and reduces feeding costs. Aragão et al (2012) evaluated corn grains replacement with MSM in sheep diets and found no effects on nutrient intake, even with 100% replacement, demonstrating its acceptability. These results may indicate that increasing MS level more than 30% in the diet may has no effect on growth performance of the animals, because MS up to 30% in our study resulted in the best productive performance of kids.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors studied the effect of MS inclusion in the diet on growth performance of sheep (Aragão et al, 2012), goats (Silva et al, 2016), and rabbit (Teye et al, 2020). The information on the influence of MS replacement in the diets on reproductive performance of small ruminants is rare.…”
Section: Introductionmentioning
confidence: 99%
“…In general, mango fruit is rich in carbohydrates and organic acids, which are important energy and flavor providers, with volatile compounds as the factors responsible for the flavor (Liu et al, 2013). Aragão et al (2012) evaluated corn replacement with mango meal in sheep diets and found no effects on nutrient intake, even with 100% replacement, demonstrating its acceptability. On the other hand, Cavalcante et al (2006) reported that inclusion of dehydrated mango above 36.1% DM caused a decrease in nutrient intake of sheep.…”
Section: Introductionmentioning
confidence: 99%